Skin prick test results in patients with chronic allergic rhinitis: Housewives are risky occupational group for the development of allergic rhinitis due to house dust mites - Mustafa Turkkani; Tarkan Ozdemir; Benan Kasapoglu; Cigdem Ozdilekcan; Fuat Erel (Journal of Contemporary Medicine, 2019)
Background/Aims: Allergic Rhinitis (AR) is a common disorder that negatively effects the quality of life with symptoms due to the inflammation of nasal epithelium. Objective of this study is to determine the general demographical and clinical features of patients with AR, who had positive skin prick test (SPT) results.  Methods: Patients diagnosed as AR with positive SPT results were analyzed. The allergens tested were: grasses, cereals+grasses , trees 1 (early flowering), trees 2 (late flowering), house-dust mites ( Dermatophagoides pteronyssinus (DP), Dermatophagoides farinae (DF), tyrophagus putrescentiae (TP), lepidoglyphus destructor (LD) and acarus siro (AS). Results: Of the total 202 patients, 145  female (with a mean age of 32.42 ±12.81 years) and 57  male (with a mean age of 28.44 ± 11.5 years) were included in the study. The most common allergens determined were; DF, DP, cereals+grasses and grasses. Tyrophagus significantly was more common in females (p:0.04). Nasal discharge, dyspnea, itching and weakness-tiredness were reported to be more common in females compared with males. DF, DP, TP and LD were statistically significantly more common in housewives (p lt;0.05). Dyspnea, wheezing and itching were statistically significantly more common in housewives (p lt;0.05).Conclusions: Housewives are risky occupational group for the development of allergic rhinitis due to house dust mites